ChemInform Abstract: Haenamindole, an Unusual Diketopiperazine Derivative from a Marine‐Derived Penicillium sp. KCB12F005. Issue 11 (February 2016) - Jang, Jae‐Hyuk; et al.,
Abstract: Haenamindole (I) possesses benzyl‐hydroxypiperazindione and phenyl‐pyrimidoindole ring systems in the molecule and shows no cytotoxic activities against Hep‐3B, HeLa, K562, and HL60 cell lines and no antimicrobial activities against Escherichia coli, Bacillus cereus, Staphylococcus aureus, and Salmonella enteritidis.